Development and validation of simulation software for RTM and VARTM processes - Kim, Peter Jong Ho (University of Ottawa (Canada), 2010)
Liquid Composite Moulding (LCM) identifies a group of composite manufacturing processes which have become conventional choices in industry due to their versatility and economic advantages. Resin Transfer Moulding (RTM) and Vacuum Assisted Resin Transfer Moulding (VARTM) have established themselves as the two main LCM options. In this thesis, a Finite Difference Method (FDM) approach is developed and implemented for predicting the flow of resin during the filling stage of RTM and VARTM. For RTM filling simulation, the discretized partial differential equations are stored in a matrix and solved using a standard numerical solution approach of Lower-Upper Decomposition. For VARTM filling simulation, solutions are obtained using an iterative method. These two different approaches were used as a result of physical differences between the two manufacturing processes, and also for investigation purposes. The RTM simulation software is capable of simulating flat moulds of any shape and the user can define any positions for the multiple inlet ports and multiple outlet vents. The user controls all the critical parameters for the process such as permeability, viscosity and porosity. Impermeable walls can be inserted in any position in order to simulate complex geometries. The distribution of resin pressure in the cavity can be seen in color scale as well as in actual numbers along with the fill time. Validation of the software was performed by running several RTM experiments and comparing the experimental and simulated flow patterns, as well as the fill times. The VARTM simulation software is developed in 1D where the important parameters such as permeability and porosity behave as variables. The governing equations are developed and discretized. The 1D solution is compared visually and numerically other results obtained from a creditable source.
Keywords: Engineering, Mechanical.